If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2(3-a)=-(3a-2)
We move all terms to the left:
2(3-a)-(-(3a-2))=0
We add all the numbers together, and all the variables
2(-1a+3)-(-(3a-2))=0
We multiply parentheses
-2a-(-(3a-2))+6=0
We calculate terms in parentheses: -(-(3a-2)), so:We get rid of parentheses
-(3a-2)
We get rid of parentheses
-3a+2
Back to the equation:
-(-3a+2)
-2a+3a-2+6=0
We add all the numbers together, and all the variables
a+4=0
We move all terms containing a to the left, all other terms to the right
a=-4
| 153=b+64 | | -4/3n=8 | | a-12+2a+a+16=180 | | -7k-21=14 | | -8b+3b=5b+8 | | -2b+-1=5 | | 0.002+0.008(8-m)=1.78 | | 18z=756 | | 3x+21=7x+6 | | -3.2-m=5 | | a–12+a+16+2a=180 | | 5c-4c+1=12 | | -18=-9-3y | | 10x2-60x=0 | | -8x+6x=-7+12 | | 3x+4x–9=33 | | 53x+2+2x=7x-20 | | 17x=17-1 | | Q(x)=2x4–8x3-2x2+4 | | 3b-14=-2b+16 | | -33x-4=2x+23 | | .36(x-50)=200 | | ‐8(‐3m‐3)=96 | | P(x)=4x3–3x2+x–2 | | 12/5=12x | | P(x)=4x3–3x2+x–2; | | -2s-7=7s-8+1 | | 12n=6=-3n-9 | | -80+x=7x+58 | | u+28+u+26+88=180 | | 21+r=66 | | -5x+18=3x+2 |